Clinical Outcome of Preterm Neonates with Respiratory Distress Syndorme on Continuous Positive Airway Pressure - Sijad-Ur- Rehman; Quratul Ain; Wahid Ali; Romana Bibi; Sohail Ashraf; Kulsoom Iqbal (Journal of Bahria University Medical and Dental College, 2022)
Objectives: To evaluate the clinical course in preterm neonates with Respiratory Distress Syndrome on bubble Continuous Positive Airway Pressure along with their outcome during stay in hospital. Study Design and Setting: A descriptive case study at the NICU was carried out at Bacha-Khan Medical Complex Swabi from December 2020 to December 2021. Methodology: Respiratory Distress Syndrome was diagnosed by following the criteria: tachypnea (> 60 breaths/min), subcostal retraction and saturation <92%. Clinical course was assessed by mean length of hospital stay from the day of admission to the day of discharge. Outcome was assessed by means of switching the baby to mechanical ventilation by failing CPAP therapy by not maintaining O2 saturation > 92% and tachypnea > 60 breaths/min on 10cm maximum pressure of H2O. CPAP response were noted. Results: Total of 100 patients enrolled in our study, 56 patients were male and 44 patients were female. Mean age was 1.24+0.04days. Mean gestational age of babies was 31.18+0.170weeks. Mean weight of babies was 2.035+0.023kg. Mean hospital stay was 15.05+0.237days. Out of 100 patients included in study 76% babies needed ventilatory support during hospital stay and 24% babies recovered from respiratory distress syndrome without need of ventilator support. Conclusion: Respiratory Distress Syndrome is a fatal complication in Preterm neonates in Neonatal Intensive Care Unit. Respiratory assistance done through continuous positive airway pressure has shown encouraging results in management by preventing complications, mechanical ventilation need, less hospital stay and preventing mortality